PENDEKATAN ANALISIS JALUR UNTUK PERCEPATAN ADOPSI AYAM KUB MELALUI MEDIA ELEKTRONIK - Wahyuningrum, Retno Dwi; Gunawan, nFN (Informatika Pertanian, 2016)
An effective media dissemination is through electronic media, which includes radio and television. Yet, the farmer character was also influenced to dissemination process. The aim of this studyimproved dissemination method that consider the charactersaudience of radio and television. The study was conducted to 114 respondents, which consist of 57 recipients of the information about KUB chicken through radio and 57 recipients through television media. The respondents was simple randomly selected 50% from total members of each 4 farmer breeder groups, which are 2 groups from Sleman Regency and 2 groups from Bantul Regency. The research was done on July â November 2014. Some observed variables was the farmer characters (age, gender and level of education), knowledge, attitude and farmer motivation for KUB chicken adoption. The knowledge, attitude and respondents motivation were evaluated using questionnaire, which was taken after the respondents received the information through radio or television. The score of questionnare was stated to the interval data, which used Likert scale. Validity andrealibility test of the questionnaire, also normality data were done by SPSS version 21. The differences influenced of radio and television to knowledge, attitude and motivation to adopt the KUB chicken were tested byt-test. The path analysis was used AMOS version 21 to test some factors that affected to the farmer knowledge, attitude and motivation. The result of study shown that television media was well disseminated of innovation than radio, because it should changed the farmer well known and wanted to adopt the KUB chicken.The radio media more suitable for male audience,that had higher motivation than woman.Since accelerating adoption of KUB chicken would be accured if the audience of television mediawere the lower educated farmer, which more motivated than the higher one.